AFRICAN HOSPITALITY IN THE ADVANCEMENT OF CHRISTIANITY IN NIGERIA - Nnadi , Fabian Uzochukwu; Iheanacho , Ambrose Onyeka; Ngwoke , Peace; Ezugwu, Joy Onyinyechukwu; Onah , Tobias Chibuike; Ejem , Emeka; Alison , Chidimma. J; Ugwueje , Kenneth; Ekwueme , Stella Chinweudo; Ike , Rosemary; et al. (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
This paper argues that African hospitality helped advance Christianity in Africa, especially in Nigeria. The type of hospitality enjoyed by the early missionaries like free lands, houses, eating together with guests, and sacrificing your life for your visitor’s safety in those days are no longer the type of hospitality that is seen today in our society. There is a need for Africans to return to their initial hospitable nature that attracted foreigners to their land. What informed the choice of this paper is that the type of hospitality enjoyed by visitors to African lands has changed and is no longer the same. Using historical and phenomenological methods of research and thematic method of data analysis to analyze the data, the findings are that poverty, the threatening effect of the European lifestyle of individualism, the egocentric nature of people in the society today and the lack of communalism in the lifestyle of Africans cause the problem of lack of hospitality in Africa today. The paper therefore recommends that Africans should guard this cultural heritage (i.e. hospitality) that their forefathers bequeathed to them.